Contextualizing Islamic Legal Perspectives on Fruit Theft in Perenggan (Borderlands): A Case Study in Kuala Tungkal, Indonesia - Nurul Hidayah Tumadi; Liana Masruroh; Iffatul Umniati Ismail; Mumtaz Mumtaz; Mustakim Mustakim; Arwansyah Kirin; Raveenthiran Vivekanantharasa (Jurnal Ilmiah Mizani: Wacana Hukum, Ekonomi Dan Keagamaan, 2025)
The phenomenon of fruit-taking in perenggan—border areas between private land and public space—represents a recurring socio-legal issue in Kuala Tungkal, Indonesia. This study aims to examine Islamic legal perspectives on the practice of picking overhanging fruit beyond property boundaries, by integrating normative analysis with empirical data rooted in local custom (‘urf). Employing a mixed-method case study design, the research involved 597 respondents through structured surveys and in-depth interviews with religious leaders, local authorities, and affected residents. The findings reveal that 88.2% of respondents had experienced fruit theft, and 57% believed the act was religiously or customarily permissible. These perceptions are shaped by economic pressures, normalized social behavior, and misconceptions of Islamic legal concepts—such as the mistaken belief that shufʿah grants harvesting rights when fruit overhangs public space. However, Islamic legal analysis affirms that such acts constitute ghaṣb (unlawful appropriation) and are prohibited (ḥarām) under sharī‘ah. In parallel, Indonesian Civil Code Article 570 affirms that produce from privately owned trees remains the legal property of the owner, even when branches extend beyond the land boundary. The novelty of this study lies in the application of contextual ijtihād, employing the theoretical framework of maqāṣid al-sharī‘ah, qiyās (analogical reasoning), istiḥsān (juristic preference), and ‘urf (customary practice) to propose humane and locally grounded legal responses. This approach enables a balanced application of the principle of wealth protection (ḥifẓ al-māl), societal welfare (maṣlaḥah), and harm prevention (mafsadah). Recommended interventions include neighbor agreements on surplus distribution, voluntary fruit-sharing arrangements, collective ethical reinforcement, and educationally oriented taʿzīr-based sanctions. The study’s primary contribution is the formulation of a context-sensitive Islamic legal model based on socio-empirical realities, offering practical guidance for fatwa development, village policymaking, and public legal education. It enriches the growing field of applied contemporary fiqh and advances productive engagement between religious texts, state law, and local wisdom